A review: differential transform method for semi-analytical solution of differential equations - Rashidi, M. M.; Rabiei, Faranak; Nia, S. Naseri; Abbasbandy, Saeid (Zielona Góra: Uniwersytet Zielonogórski)
In this article, the semi-analytical method known as the Differential Transform Method (DTM) for solving different types of differential equations is reviewed. First, basic definitions and formulas of DTM and Differential Transform-Padé approximation (DTM-Padé), which are used to increase the convergence and accuracy of DTM approximations, are discussed.
Keywords: differential transform method; differential transform-Padé approximation; semi-analytical method; differential equations; fuzzy differential transformation method; gS-differentiability